La prévention des risques industriels, frein ou moteur du développement économique ? - Emmanuel Martinais (Développement Durable et Territoires)
This article deals with the preparation of the technological risks prevention plan (a French land-use planning regulation tool called PPRT) of the « chemicals valley », an industrial platform located to the south of Lyon (France). It focuses on the concrete work of the stakeholders, the forum that they establish to decide together and the problems they have to solve to achieve their goals with respect to the regulation. This immersion in the heart of the procedure gives us the opportunity to discover that while the prevention of industrial risks is often thought of as being a factor that undermines economic development, in this situation it has acted as the « engine » of an important revitalization of the Chemicals valley industrial platform, whilst establishing the legal and technological conditions that allow heavy industry to remain present in this heavily urbanized area.